(untitled) (Homoeopathy for All, 2024)
Homoeopathic Pharmacy has its own distinct presence attributable to its specific techniques of preparation. Since its development homoeopathic pharmacy has embraced the latest technological advances and utilised them for improving drug manufacturing while remaining true to the core process of homoeopathic potentistation as established by Dr Hahnemann. Increasing popularity of homoeopathy has lead to simultaneous increase in requirement of medicines. Dr Hahnemann repeatedly asserted on need of genuine good quality medicine. His focus on good quality raw materials and strict observance of preparation techniques is evident in his writings. Development of pharmacopeias further strengthened standardization in homoeopathic pharmacy.